NURSES, KNOWLEDGE AND PRACTICE TOWARDS PRESSURE ULCER PREVENTION IN GOVERNMENTAL HOSPITALS IN AKRE DISTRICT, KURDISTAN REGION OF IRAQ - AHMED, SRUD MANAF; TAHIR, ARAZOO ISSA; AL-BANNA, DARA ABDULLAH; SALIH, JIHAN FAKHRI (Journal of Duhok University, 2023)
A pressure ulcer is an injury to the skin and underlying tissues brought on by pressure, shear, or friction, it generally develops over a bony prominence and manifests as either an open sore or a non-healing wound. The study sought to evaluate nurses’ knowledge and practices regarding pressure ulcer prevention in the Akre district of Iraq. A cross-sectional study including 114 eligible nurses from two general hospitals was undertaken from July 26 to August 28, 2022.The study’s participants were chosen using a convenience sampling technique. The knowledge and practice of nurses were evaluated using a structured questionnaire that had been adopted. To evaluate connections between knowledge and practice, descriptive statistics, tables, Chi-Square tests, and Fisher’s exact tests were performed using SPSS version 26. Among all nurses involved in this study, (74.6%) had acceptable cores of pressure ulcer prevention knowledge, and (75.4%) had acceptable practice. The findings of this study showed that respondents had enough information about pressure ulcer prevention, which may have contributed to their acceptable conduct (p> 0.05). The working setting had a significant association with nurses’ knowledge and practices. Also, nurses’ practices were significantly associated with job satisfaction and heavy workload. Nurses’ pressure ulcer prevention knowledge and practice in this study were satisfactory. Increasing training frequency in public hospitals can help improve a thorough understanding of pressure ulcers among nurses in the Kurdistan region, Iraq